Leukotriene receptor blockade as a life-saving treatment in severe Bronchopulmonary dysplasia - Rupprecht, Thomas; Rupprecht, Christian; Harms, Dieter; Sterlacci, William; Vieth, Michael; Seybold, Kathrin (Respiration, 2014)
Background: Bronchopulmonary dysplasia (BPD) is a major cause of mortality and morbidity in infants with an extremely low birth weight. Because there is no effective therapy, the mortality of this condition in severely affected patients is high. Therapeutic blocking of the leukotriene system seems to be a logical approach due to the known pathophysiology of BPD.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Bronchopulmonary dysplasia; Montelukast; Neonatology; Pediatrics